An assessment of nitrogen concentrations from spectroscopic measurements in the JET and ASDEX upgrade divertor. (January 2019) - Henderson, S.S.; Bernert, M.; Brezinsek, S.; Carr, M.; Cavedon, M.; Dux, R.; Gahle, D.S.; Harrison, J.; Kallenbach, A.; Lipschultz, B.; Lomanowski, B.; Meigs, A.; et al.
Highlights: Higher experimental N divertor concentrations in ASDEX Upgrade and JET are found with lower divertor temperatures. With increasing power entering the separatrix, a higher N concentration is required to achieve the same detachment state. N concentrations in partially detached plasma tentatively agree with predictions from the Goldston detachment scaling law. N concentrations from spectroscopy and D2 and N2 flux ratios agree within uncertainty when vessel surfaces are fully-loaded. Abstract: The impurity concentration in the tokamak divertor plasma is a necessary input for predictive scaling of divertor detachment, however direct measurements from existing tokamaks in different divertor plasma conditions are limited. To address this, we have applied a recently developed spectroscopic N II line ratio technique for measuring the N concentration in the divertor to a range of H-mode and L-mode plasma from the ASDEX Upgrade and JET tokamaks, respectively. The results from both devices show that as the power crossing the separatrix, Psep, is increased under otherwise similar core conditions (e.g. density), a higher N concentration is required to achieve the same detachment state. For example, the N concentrations at the start of detachment increase from ≈ 2% to ≈ 9% as Psep is increased from ≈ 2.5 MW to ≈ 7 MW. These results tentatively agree with scaling law predictions (e.g. Goldston et al .) motivating a further study examining the parameters which affect the N concentration required to reach detachment. Finally, the N concentrations from spectroscopy and the ratio of D and N gas valve fluxes agree within experimental uncertainty only when the vessel surfaces are fully-loaded with N.